Rituximab experience from a single centre for patients with rheumatoid arthritis-related interstitial lung disease: Rituximab in RA-ILD - Sahin Eroglu, Didem; Colaklar, Anil; Baysal, Serdar; Torgutalp, Murat; Baygul, Asaf; Yayla, Mucteba Enes; Sezer, Serdar; Uzun, Caglar; Ozdemir Kumbasar, Ozlem; Turgay, Tahsin Murat; Kinikli, Gulay; Ates, Askin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Objective. To demonstrate the effects of rituximab (RTX) in patients with rheumatoid arthritis-related interstitial lung disease (RA-ILD). Methods. A total of 165 patients who used RTX for the management of rheumatoid arthritis were retrospectively scrutinised. Among these, 26 patients diagnosed with RA-ILD were analysed (61.5% male, mean age at RTX infusion 61.4 ± 6.5 years). To evaluate the efficacy of RTX on lung response, patients with pulmonary function test results and/or thorax computed tomography (chest-CT) of pre- and post-RTX were compared. Disease progression was defined as either a decline of ≥10% in forced vital capacity (FVC) and/or a decline of ≥15% in diffusion capacity of carbon monoxide (DLCO), or an increase of parenchymal involvement on chest-CT images according to the radiologists’ assessment. Results. Among 26 patients, the most common radiologic pattern was usual interstitial pneumonia (42.3%), followed by non-specific interstitial pneumonia (38.5%). Data for lung response was available in 20 patients. Median pre- and post- RTX DLCO values were 71.0% (60.0-77.0) and 63.0% (47.0-74.0), respectively (p= 0.06). Median pre- and post-RTX FVC values were 74.0% (61.0-99.0) and 84.0% (63.0-100.0), respectively (p= 0.28). Overall, stabilization or regression of RA-ILD was provided in 13 (65.0%) patients, whereas 7 patients had progressive RA-ILD. Post-RTX, 5 patients were diagnosed with RA-ILD. Conclusion. Our results suggest that RTX is effective in achieving stabilization or even improvement of RA-ILD. However, considering that it does not cause regression in every patient and some develop RA-ILD under RTX, we still need more effective treatment options.